Políticas e imaginarios del agua - Nun queremos la corta! Nun queremos acá la barraige!: Politicizing hydropower plants in Portugal through a (renewable) energy colonialism lens - Batel, S. (Modernidad, energía y poder. Una historia cultural ecoenergética del sur de Europa, 2023)
The recent sale of three large-scale hydroelectric power dams in Terra de Miranda (Northeast of Portugal) to an international consortium, gave rise to local protests reopening old wounds of communities affected by these ‘cuts’ (la corta in mirandês, the regional language) in the rivers, due to related injustices in the deployment of the dams and throughout time. This controversy prompted us to inquire into the imaginaries of water and energy that emerged in these and other dams-affected communities from the impositions and promises made about these infrastructures by the State (from the dictatorship to democracy), and that often implied the dispossession and controlling from afar of rural territories and of their socio-ecological systems. As such, this paper will, based on the framework of renewable energy colonialism, investigate and discuss the spatio-temporalities of hydrocolonialism in Portugal throughout time, from the 1950’s (under the dictatorship) to the present, and examples of resistance. We undertake a psychosocial historiography of selected large-scale hydroelectric power plants in Portugal, performed via archival data, namely public TV news segments and newspapers’ articles, and interviews with participants of the Terra de Miranda movement. Our analysis illustrates the particular ways through which hydrocolonialism has been enacted –discursively, infrastructurally, and psychosocially –in rural areas in Portugal, across different socio-political regimes, and also how it can be contested.